2017
DOI: 10.1002/ange.201710053
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Suzuki Biaryl Coupling of Aryl Halides

Abstract: Readily accessed cobalt pre-catalysts with N-heterocyclic carbene ligands catalyze the Suzuki cross-coupling of aryl chlorides and bromides with alkyllithium-activated arylboronic pinacolate esters.P reliminary mechanistic studies indicate that the cobalt species is reduced to Co 0 during the reaction.The palladium-catalyzed cross-coupling of organoboronic acids or esters with organic halides or related substrates-the Suzuki reaction-is ap owerful and very widely exploited method for the formation of biaryl co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Indeed, in the racemate synthesis campaign with 4,4′‐( t Bu) 2 ‐bipyridine as the ligand, we observed quantitative formation of products 3 a and 3 b starting respectively from 2 h and 2 i [43] . Thus under the reaction conditions hereby explored, debromination readily occurred in the presence of a neutral ligand possibly due to a more facile access to low valent Co‐species, in agreement with previously observed reactivity [44] . Substituents on the aromatic ring could be placed in para‐ or meta ‐positions ( 3 k – 3 l ) without resulting in significant changes in reactivity and enantioselectivity.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, in the racemate synthesis campaign with 4,4′‐( t Bu) 2 ‐bipyridine as the ligand, we observed quantitative formation of products 3 a and 3 b starting respectively from 2 h and 2 i [43] . Thus under the reaction conditions hereby explored, debromination readily occurred in the presence of a neutral ligand possibly due to a more facile access to low valent Co‐species, in agreement with previously observed reactivity [44] . Substituents on the aromatic ring could be placed in para‐ or meta ‐positions ( 3 k – 3 l ) without resulting in significant changes in reactivity and enantioselectivity.…”
Section: Resultssupporting
confidence: 87%
“…White solid (110 mg, 49% yield); mp 104–105 °C, 22 R f = 0.26 (hexane/ethyl acetate 2/3). 1 H NMR (400 MHz, CDCl 3 ) δ: 7.63–7.59 (m, 4H), 7.53–7.42 (m, 4H), 7.39–7.35 (m, 1H), 3.09 (brs, 6H).…”
Section: Methodsmentioning
confidence: 99%
“…44 A recent report by Bedford even showed that the three-coordinate iron(0) and cobalt(0) complexes [(IMes)Fe(η 2 :η 2 -dvtms)], [(sIPr)Co(η 2 :η 2 -dvtms)], and [(sIPr)Co(η 2 -norbornene) 2 ] can be formed upon the interaction of MCl 2 (M = Fe, Co) with NHCs, alkenes, and n-butyllithium-activated phenylboronic pinacolate ester, wherein the borane reagent seems to serve as a net reductant. 45,46 It is worth mentioning that in addition to these reductive methods, the formation of fourand three-coordinate cobalt(0) and iron(0) complexes via ligand replacement and reductive elimination reactions can also be found in the literature. Grubbs reported the preparation of the four-coordinate complex [(BAC) 2 Fe(η 2 -COT)] (COT = cyclooctatetraene) from the reaction of Fe(COT) 2 with BAC (Chart 1).…”
Section: ■ Synthesismentioning
confidence: 99%